2014
DOI: 10.1111/jtxs.12093
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Calcium Hydroxide and Konjac Glucomannan (KGM) on the Thermomechanical Properties of Buckwheat Flour and the Quality of Buckwheat Noodles

Abstract: Based on the results of previous studies, 0.4% calcium hydroxide and varying proportions of konjac glucomannan (KGM) were used to optimize the rheological behavior of buckwheat flour and the quality of buckwheat noodles in this study. The results revealed that the thermomechanical properties of buckwheat flour were markedly improved by KGM and calcium hydroxide, as shown in detail by the increased stability and decreased degree of protein weakening in the buckwheat dough. Adding 1.5% KGM and 0.4% calcium hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The study showed that the KGM jelly drinks containing κ-carrageenan were more acceptable and achieved a higher consumer purchase rate than those containing XG. Noodle is one of staple foods in china, KGM and 0.4% calcium hydroxide had been used to improve the quality of buckwheat noodles by Han et al [ 64 ], the study showed that KGM and 0.4% calcium hydroxide improved the tensile strength and firmness of the cooked noodles, the presence of calcium hydroxide promoted the formation of gel networks in the noodles, and further resulted in better cooking and sensory qualities.…”
Section: Application Of Kgm Gelmentioning
confidence: 99%
“…The study showed that the KGM jelly drinks containing κ-carrageenan were more acceptable and achieved a higher consumer purchase rate than those containing XG. Noodle is one of staple foods in china, KGM and 0.4% calcium hydroxide had been used to improve the quality of buckwheat noodles by Han et al [ 64 ], the study showed that KGM and 0.4% calcium hydroxide improved the tensile strength and firmness of the cooked noodles, the presence of calcium hydroxide promoted the formation of gel networks in the noodles, and further resulted in better cooking and sensory qualities.…”
Section: Application Of Kgm Gelmentioning
confidence: 99%
“…However, the loss rate increased when the added amount reached 30%. This finding can be explained by the formation of a hydration network between starch molecules on the surface of starch particles, and stably adsorbing them into the noodle matrix (Han et al., 2014 ). The addition of excess starch acetates weakened the connection between gluten networks in noodles, which might lead to the dissolution of water‐soluble substances.…”
Section: Resultsmentioning
confidence: 99%
“…Konjac glucomannan (KGM), a natural non-ionic polysaccharide isolated from the root tuber of the Amorphophallus konjac plant, is composed of D-glucose and D-mannose units through ⊎-1,4-linkages and acetylated at the C-6 position for every 19 glucose units. 7 The unique structure of KGM can facilitate gelling, thickening behavior, and water-holding capacity, which would expand its application in starchy foods. 8,9 It has also been used as a crystallization inhibitor to prevent starch retrogradation.…”
Section: Introductionmentioning
confidence: 99%